Analisis Tren Pendaftaran Siswa Alwashliyah Marbau Menggunakan Big Data - Putra, Mhd Aftiansyah; Mulawarman, Marchelius; Aziz, Abdul; Sitorus, Sahat Parulian (Universitas Labuhanbatu, 2026)
This study aims to analyze student enrollment trends at the Alwashliyah Marbau Education Foundation over the past five years, focusing on the MTS, MAS, SMK-1, and SMK-2 levels. The analysis shows that the SMK-1 vocational program has seen a 15% increase in enrollment annually, while the MAS program has seen a significant decline of up to 20% in the last year. The majority of enrollees come from the Marbau area (70%), indicating a certain geographic dominance in student recruitment. Correlation tests identified a positive relationship between digital promotion and enrollment growth at the SMK level. Key recommendations include increasing the intensity of digital promotion, adjusting the curriculum based on job market needs, and evaluating promotional strategies for programs with declining trends. The resulting data visualization also provides insights to support recruitment strategy optimization.